Serum pentraxin 3 as a biomarker of hepatocellular carcinoma in chronic hepatitis B virus infection - Deng, Huan (Sci Rep, 2020)
Biomarkers for early diagnosis of hepatocellular carcinoma (HCC) are needed in chronic hepatitis B virus (HBV) infection, a leading cause of HCC. We evaluated whether measurement of serum pentraxin 3 (PTX3) could improve diagnosis of HCC in chronic HBV infection. Data from patients with HBV-related chronic hepatitis (n = 159), cirrhosis (n = 99) and HCC (n = 107), and healthy controls (n = 151) were analyzed. Serum PTX3 concentration was measured by immunoassay. Area under the receiver operating characteristic curve (AUC) was applied to assess diagnostic accuracy. PTX3 levels were significantly higher in HBV patients than in healthy controls (P < 0.001) and in HCC than in chronic hepatitis (P < 0.001) or cirrhosis patients (P < 0.001). PTX3 was an independent risk factor of HCC [odds ratio (OR) 1.617, P < 0.001] and could distinguish HCC in chronic HBV infection [cutoff 9.231 ng/mL, AUC 0.929 with 95% confidence interval (CI) of 0.898–0.953], including α-fetoprotein (AFP) negative [cutoff 8.985 ng/mL, AUC (95%CI) 0.947 (0.908–0.973)] and early-stage HCC [cutoff 9.359 ng/mL, AUC (95%CI) 0.920 (0.885–0.947)]. Combination of PTX3 with AFP improved the discrimination of early HCC from chronic HBV infection [AUC (95%CI) 0.948 (0.918–0.970)]. In short, PTX3 measurement could identify HCC, including AFP-negative and early-stage HCC, in chronic HBV infection.